2019
DOI: 10.1186/s12872-019-1106-3
|View full text |Cite
|
Sign up to set email alerts
|

Safety of in-hospital insertable cardiac monitor procedures performed outside the traditional settings: results from the Reveal LINQ in-office 2 international study

Abstract: Background Historically, the majority of insertable cardiac monitor (ICM) procedures were performed in the cardiac catheterization (cath) lab, electrophysiology (EP) lab, or operating room (OR). The miniaturization of ICMs allows the procedure to be relocated within the hospital without compromising patient safety. We sought to estimate the rate of untoward events associated with procedures performed within the hospital but outside the traditional settings and to characterize resource utilization,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
2
4
0
Order By: Relevance
“…Two infections resolved with oral antibiotic treatment, and one resulted in explant of the ICM. This low rate of infection is consistent with other reports of low infection rates (0%–1.6%) 11 , 12 , 13 , 14 , 15 …”
Section: Discussionsupporting
confidence: 93%
“…Two infections resolved with oral antibiotic treatment, and one resulted in explant of the ICM. This low rate of infection is consistent with other reports of low infection rates (0%–1.6%) 11 , 12 , 13 , 14 , 15 …”
Section: Discussionsupporting
confidence: 93%
“…The median time from incision to closure was 4.0 minutes (IQR, 2.3–6.2 minutes) as compared to 4.0 minutes (IQR, 3.0–6.0 minutes) reported in another state-of-the-art ICM with a similar cross-sectional profile (Reveal LINQ; Medtronic Inc, Minneapolis, MN). 10 In 18.5% of our patients, the ICM was inserted in a consultation room instead of a catheterization lab or operation theatre. Miniaturization of ICMs enables the procedure to be relocated to this new environment, giving hospitals flexibility in planning the use of their facilities without compromising patient safety or outcomes.…”
Section: Discussionmentioning
confidence: 97%
“…Miniaturization of ICMs enables the procedure to be relocated to this new environment, giving hospitals flexibility in planning the use of their facilities without J o u r n a l P r e -p r o o f compromising patient safety or outcomes. [9][10][11][12] From the patients' perspective in a large-cohort study described by Rogers et al, 11 far more patients perceived the procedure location to be "very convenient" when it was performed in-office (85%) than when it was performed in hospital (29%).…”
Section: Simplicity Of the Insertion Proceduresmentioning
confidence: 99%
“…In our practice of a 1000 bed tertiary care facility and EP lab which implants approximately 250 loop recorder devices per year [9], we have a very low side effect profile, much as is seen nationally. As in previous loop recorder studies [10] our side effect profile includes localized bleeding (small hematoma), localized skin changes (irritation and or rash) and localized infection or mild pain at the insertion pocket site [11]. These side effects are limited to a less than1-2% chance of occurrence and are easily managed with short term compression, skin care and acetaminophen or ibuprofen.…”
Section: Potential Side Effect Profilementioning
confidence: 94%
“…This literature review examined advantages of an ILR, evolving ILR technology, possible skin changes or rashes, increased pain at the insertion site, migration of the loop recorder and dislodgement of the loop recorder. This search proved to be challenging as the LINQ loop recorder insertion is associated with such a low complication rate and considered a smooth and relatively troublefree procedure [10]. The literature review revealed cases which included the term "pain" but did not directly relate to the pocket site pain.…”
Section: Literature Reviewmentioning
confidence: 99%